Heart Involvement in Systemic Lupus Erythematosus - Andree Kurniawan; Nata Pratama Hardjo Lugito (Fakultas Kedokteran Universitas Pelita Harapan, 2018)
Pericardial effusion is considered as one of criteria to diagnose systemic lupus erythematosus (SLE) based on American Rheumatism Association (ARA) criteria. There is limited data about the incidence and characteristic pericardial effusion in SLE patients in our country. The aim of this study is to report and assess the incidence of and characteristic heart involvement in SLE. This is cross-sectional study conducted in secondary referral hospital in Tangerang county, west part of Jakarta, capital city of Indonesia. We evaluated from medical record and echocardiogram data from 2013-2015 patients diagnosed with SLE according to ARA criteria. From 33 SLE medical records reviewed, we found 13 patients (40%) with pericardial effusions. All patients were in active stage. Clinical assessment and transthoracic echocardiogram were used to diagnose pericardial effusions. Eighty percent pericardial effusion positive patients had minimal effusion. The others had moderate effusion. No tamponade patients were recorded. Ninety six percent patients were female with median age 24(13-51) years old. Three patients were reported having pulmonary arterial hypertension. One patient had thrombus in left ventricle. All patients had clinical symptoms of cardiac such as heart failure and chest pain. For the conclusion, the incidence of pericardial effusion in SLE patient was 40 percent. Eighty percent patients had minimal effusion. All patients had cardiac symptoms related.